EVALUATION OF AQIDAH AKHLAK LEARNING ON THE CHARACTER OF CLASS VIII STUDENTS AT SMP AL BAROKAH, PURWAKARTA REGENCY, ACADEMIC YEAR 2021/2022 (Jurnal Sosial Humaniora dan Pendidikan, 2022)
Learning aqidah morality greatly affects the character of students, because by educating good character, students will understand how to foster and guide themselves in everyday life. From the results of the pre-survey, it is stated that there are still students who do not have a good personality in their lives, even though basically they have been given education in their schools. Meanwhile, this study aims to determine the effect of moral learning on the character of students at SMP AL BAROKAH Purwakarta. This type of research is quantitative research. The total population in this study were students of class VIII at SMP AL BAROKAH Purwakarta, totaling 200 students. as for the sampling technique in this study using a random sampling technique that is taking 20% of the total population so that a sample of 40 students is obtained. This study uses data collection tools in the form of observation and documentation. Thus, the hypothesis that the authors propose is accepted and Ho is rejected. So the conclusion is that there is an effect of moral learning on the character of class VIII students at SMP AL BAROKAH Purwakarta for the 2021/2022 academic year.